2014
DOI: 10.1088/0004-637x/786/2/106
|View full text |Cite
|
Sign up to set email alerts
|

Intergalactic Medium Emission Observations With the Cosmic Web Imager. I. The Circum-Qso Medium of Qso 1549+19, and Evidence for a Filamentary Gas Inflow

Abstract: The Palomar Cosmic Web Imager (PCWI), an integral field spectrograph designed to detect and map low surface brightness emission, has obtained imaging spectroscopic maps of Lyα from the circum-QSO medium (CQM) of QSO HS1549+19 at redshift z=2.843. Extensive extended emission is detected from the CQM, consistent with fluorescent and pumped Lyα produced by the ionizing and Lyα continuum of the QSO. Many features present in PCWI spectral images match those detected in narrow-band images. Filamentary structures wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
124
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 116 publications
(130 citation statements)
references
References 62 publications
6
124
0
Order By: Relevance
“…The typical detection rate of giant nebulae (i.e., with projected sizes larger than 100 pkpc) around radio-quiet quasars in these NB surveys is less than 10% considering both deep LRIS/Keck data (S. Cantalupo et al 2016, in preparation) and shallower surveys using GMOS (Arrigoni Battaia et al 2016). This low detection rate is also found by other independent surveys using broader NB filters on LRIS/Keck (Martin et al 2014).…”
Section: Introductionsupporting
confidence: 86%
See 4 more Smart Citations
“…The typical detection rate of giant nebulae (i.e., with projected sizes larger than 100 pkpc) around radio-quiet quasars in these NB surveys is less than 10% considering both deep LRIS/Keck data (S. Cantalupo et al 2016, in preparation) and shallower surveys using GMOS (Arrigoni Battaia et al 2016). This low detection rate is also found by other independent surveys using broader NB filters on LRIS/Keck (Martin et al 2014).…”
Section: Introductionsupporting
confidence: 86%
“…This result seems to be in stark contrast with previous narrow-band and spectroscopic surveys for bright radio-quiet quasars at highredshift. These studies have found detection rates of giant nebula less than 10% using NB imaging at < < z 2 3 (Cantalupo et al 2014;Martin et al 2014;Hennawi et al 2015;Arrigoni Battaia et al 2016), while spectroscopic surveys at any redshift have found exclusively smaller nebulae (<60 pkpc) and only in about 50% of the cases (North et al 2012;Fathivavsari et al 2015). Because all these surveys-including our MUSE observations-reached a similar depth, the origin of this discrepancy must be searched for somewhere else.…”
Section: Why Such a High Detection Ratementioning
confidence: 73%
See 3 more Smart Citations